Museums as Places: Two review cases and a transdisciplinary perspective - Nina GJOCI; Joshua D. ATKINSON (E-REA)
In this essay, we theorize the differences and similarities between rhetorical and cultural geographic approaches to the study of one example of a memory place: museums. We use two major museum research studies to illustrate the findings. We argue that the relationship between memory and place render one major difference between these approaches: vertical versus horizontal readings. We refer to reading as the range of practices employed when studying places. Vertical reading comes mainly from the rhetoricians’ emphasis on hierarchy of meaning and horizontal reading comes mainly from geographers’ emphasis on representation and flexibility. Despite these differences, the disciplines share important similarities with respect to conceptualization and approach; both maintain that places are selective, contextual, and constitutive of identity. Studying museums as places requires both approaches, as we must attend to both how places are made (geographical) and what they do (rhetorical).